Susceptibility of house mouse carriers of Tyr139Cys and Leu128Ser/Tyr139Cys VKOR variants to difenacoum. Issue 2 (3rd April 2023) - Blažić, Tanja; Jokić, Goran; Esther, Alexandra; Đedović, Suzana
Abstract: After the vkorc1 gene was first identified, changes occurring in the gene have been considered one of the main reasons of reduced susceptibility of house mice to anticoagulants. A no-choice feeding test was conducted according to standard EPPO (2004 ) methodology. Animals were fed for 21 days on baits containing difenacoum 0.005%. All animals were bromadiolone-resistant. Seven months earlier, all test animals had survived a 21-day bromadiolone (0.005%) no-choice feeding test, and sequencing of their vkorc1 gene had revealed the presence of Tyr139Cys and Leu1258Ser/Tyr139Cys VKOR variant. There were no survivors in the no-choice difenacoum feeding test. Consumption was not affected by VKOR variant, sex or genotype. A higher lethal dose was confirmed for Leu128Ser/Tyr139Cys than Tyr139Cys carriers, for females than males, and for homozygotes than heterozygotes. Our research showed that difenacoum 0.005% was effective against house mice carrying the Tyr139Cys VKOR variant, whether it occurred independently or in combination with the Leu128Ser variant in the Vkorc1 gene.